Retention of clients in HIV oral pre-exposure prophylaxis care in Engela, Namibia - Kristiana Kosmas; Enos Moyo; Mbuzeleni Hlongwa; Perseverance Moyo; Tafadzwa Dzinamarira; Anna Shilunga (African Journal of Primary Health Care & Family Medicine, 2025)
Background: Namibia has made tremendous progress in controlling the HIV epidemic. The progress has resulted in significant incidence and AIDS-related mortality reductions. However, new infections continue to persist.